2011
DOI: 10.1097/scs.0b013e31822e633b
|View full text |Cite
|
Sign up to set email alerts
|

Nonvascularized Bone Grafting for Mandibular Reconstruction

Abstract: This retrospective study analyzes the long-term results and complications of mandibular reconstruction with nonvascularized bone grafts (NVBGs) and suggests refinements. A total of 166 patients underwent mandibular ablation and primary reconstruction between June 1990 and August 2009, of which 101 were NVBGs, 27 were vascularized bone grafts, and 38 were with functional plate reconstruction. Eighty-seven of 101 patients undergoing NVBG, having all records and followed up for a minimum of 12 months, were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 26 publications
1
50
0
2
Order By: Relevance
“…Their ability to report at an early stage of the disease and for frequent follow-up is limited [1]. Other factors like, increased intra-operative time and post operative stay, increased age and compromised medical condition of the patient are against micro vascular grafting.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Their ability to report at an early stage of the disease and for frequent follow-up is limited [1]. Other factors like, increased intra-operative time and post operative stay, increased age and compromised medical condition of the patient are against micro vascular grafting.…”
Section: Discussionmentioning
confidence: 99%
“…In our study we have done immediate reconstruction and 7 days of antibiotic therapy for every patient which resulted in optimum results. Gadre et al [1] suggested using a stay suture of nonresorbable material to fix the soft tissue to the graft or hardware reduces the dead space, hematoma formation and prevents development of additional weight beneath the reconstruction. This aids in reduction of pull and drag on the intraoral suture line and thus the dehiscence rate decreases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations